Accelerated solvent extraction of carotenoids from: Tunisian Kaki (Diospyros kaki L.), peach (Prunus persica L.) and apricot (Prunus armeniaca L.). (1st October 2015) - Zaghdoudi, Khalil; Pontvianne, Steve; Framboisier, Xavier; Achard, Mathilde; Kudaibergenova, Rabiga; Ayadi-Trabelsi, Malika; Kalthoum-cherif, Jamila; Vanderesse, Régis; Frochot, Céline; Guiavarc'h, Yann
Highlights: We extracted carotenoids from kakis, peaches and apricots cultivated in Tunisia. We used accelerated solvent extraction (ASE) for xanthophylls/carotenes extraction. A design of experiment (DoE) was used for surface responses building and optimization. Best conditions were 5 min static extraction at 40 °C with methanol/THF, 20:80, v:v. ASE appeared as a performing technic for efficient carotenoids extraction. Abstract: Extraction of carotenoids from biological matrices and quantifications remains a difficult task. Accelerated solvent extraction was used as an efficient extraction process for carotenoids extraction from three fruits cultivated in Tunisia: kaki ( Diospyros kaki L.), peach ( Prunus persica L.) and apricot ( Prunus armeniaca L.). Based on a design of experiment (DoE) approach, and using a binary solvent consisting of methanol and tetrahydrofuran, we could identify the best extraction conditions as being 40 °C, 20:80 (v:v) methanol/tetrahydrofuran and 5 min of extraction time. Surprisingly and likely due to the high extraction pressure used (103 bars), these conditions appeared to be the best ones both for extracting xanthophylls such as lutein, zeaxanthin or β-cryptoxanthin and carotenes such as β-carotene, which present quite different polarities. Twelve surface responses were generated for lutein, zeaxanthin, β-cryptoxanthin and β-carotene in kaki, peach and apricot. Further LC–MS analysis allowed comparisons in carotenoids profiles between the fruits.